EARTHQUAKE INFORMATION PUSH NOTIFICATION SYSTEM IN ANDROID APPLICATION USING GOOGLE FIREBASE - Rakhmad Maulidi; Bagus Kristomoyo Kristanto; Yohanes Dwi Listio (IJISCS (International Journal of Information System and Computer Science), 2020)
Indonesia is a country located between three tectonic plates, namely Eurasia, the Pacific and Indo-Australia, which is one of the active plates, so that there is the potential for earthquakes, which are sometimes followed by tsunami disasters. The latest accurate, precise, and trusted earthquake information is needed by all parties. For this reason, a system is needed to inform the latest earthquake so that the impact can be minimized. Departing from open data published by BMKG, which is an earthquake in real time, a push notification system for earthquake information was designed to the Android application using Google Firebase. Push notifications are adjusted for specific areas based on user wishes. When the user is in the vicinity of an earthquake-affected or surrounding area, or the location of an earthquake is in a city that is monitored by the user, the notifications that appear can be alerts. Whereas when the user is in a location that is not affected by an earthquake, the notification that appears is only as information that there is an earthquake in a certain area. After analyzing, designing, implementing and testing using the black box testing method, push notification system functionally produces results that are as expected.